The Differences of Improving Communication Ability and Mathematical Concepts Understanding between Students that Given Problem Based Learning and Discovery Learning at SMP Swasta Al-Hikmah Medan - Rennita, Oktavia Dwi (Advances in Social Sciences Research Journal, 2018)
Abstract This study aims to analyze (1) The Differences of Improving Communication Ability and Mathematical Concepts Understanding between Students that Given Problem Based Learning and Discovery Learning, (2) There is an interaction between the learning model with the students’ initial ability of mathematics (KAM) towards improving students’ communication ability and mathematical concepts understanding. The type of this research was quasi-experimental. This study was conducted at SMP Swasta Al-Hikmah. The population in this study was all students of class VIII by taking a sample of two classes. The instrument used consists of students' mathematical communication test and understanding concepts. The instruments fulfilled the requirements of content validity and high reliability, i.e. 0.789 and 0.793 respectively for mathematical communication and concepts understanding ability. Data were analyzed by the Two Way Anova test. Before using the Two Way Anova test, homogeneity and normality were tested first in this study with a significant level of 5%. Based on the results of the analysis, the results of the study were: (1) there was the difference of improving communication ability and mathematical concepts understanding between students that given problem-based learning and discovery learning, (2) there is interaction between the learning model with the students’ initial ability of mathematics towards improving students’ communication ability and mathematical concepts understanding. Keywords: mathematical communication ability, understanding of mathematical concepts, problem based learning model, discovery learning model and students’ initial ability of mathematics